Effect of intelligent controlled release anti-microbial packaging in food preservation - Samreen Latif; Anam Latif; Wisha Waheed; Amar Shankar; Jadhav Balaji; Ali Imran; Muhammad Sadiq Naseer; Fatima Tariq; Fakhar Islam; Abdela Befa Kinki (Food Production, Processing and Nutrition)
Abstract Food packaging is intended to shield foods, provide necessary food details, and make food handling easier for delivery to customers. Packaging holds pivotal importance in the elongation of shelf-life, food, and quality. Controlled Release Packaging (CRP) is an innovative method that improves quality and safety of food products during storage. This technique involves the release of active ingredients in a controlled, regulated manner. Food preservation is greatly improved by the use of intelligent controlled release antimicrobial packaging, which uses responsive systems to release antimicrobial agents in response to environmental stimuli. This novel method prevents microbial development, extending the shelf life of perishable foods while simultaneously guaranteeing food safety. This paper elucidates a critical review of CRP. Additionally, it summarizes the difficulties and potential outcomes, as well as the present state of application in several food categories. An innovative and challenging packaging technique, CRP technology attempts to maximize the antibacterial effect and preserve the standard of food items by harmonizing the delivery of active ingredients with the need for food preservation using detecting input via a stimulus. In order to serve as a reference for future research on food preservation and food packaging, this review summarizes the uniqueness of CRP, active compounds, as well as its application in different foodstuff. Graphical Abstract